Combination of Early Allograft Dysfunction and Protein Expression Patterns Predicts Outcome of Liver Transplantation From Donation After Cardiac Death - Wei, Qiang; Zhou, Junbin; Wang, Kun; Zhang, Xuanyu; Chen, Junli; Lu, Di; Wei, Xuyong; Zheng, Shusen; Xu, Xiao (Frontiers in Medicine, 2021)
Early allograft dysfunction (EAD) after liver transplantation (LT) accompanies poor prognosis. This study aims to explore the relationship between pretransplant intrahepatic proteins and the incidence of EAD, and the value of combined EAD and protein profiles for predicting recipient and graft survival prognosis. Liver biopsy specimens of 105 pretransplant grafts used for LT were collected and used for immunohistochemistry analysis of 5 proteins. And matched clinical data of donor, recipient, transplantation, and prognosis were analyzed. The incidence of EAD was 41.9% (44/105) in this cohort. Macrovesicular steatosis (P = 0.016), donor body mass index (P = 0.013), recipients' pretransplant serum creatinine (P = 0.036), and intrahepatic expression of heme oxygenase 1 (HO1) (P = 0.015) and tumor necrosis factor α (TNF-α) (P = 0.039) were independent predictors of EAD. Inferior graft and recipient prognosis were observed in patients who experienced EAD (P = 0.028 and 0.031) or received grafts with higher expression of sirtuin 1 (P = 0.005 and 0.013). The graft and recipient survival were worst in patients with both EAD and high expression of sirtuin 1 (P = 0.001 and 0.004). In conclusion, pretransplant intrahepatic expression of HO1 and TNF-α are associated with the incidence of EAD. The combination of EAD and EAD-unrelated proteins showed superiority in distinguishing recipients with worse prognosis.